Digital Signature Schemes: A Thematic Evolution from RSA/ECC to Post-Quantum and Aggregate Signatures (2015-2022) - Saputra, Imam; Mesran, Mesran (Journal of Computing and Informatics Research, 2024)
This study aims to map and quantify the thematic evolution of Digital Signature Schemes (DSS) amid the existential challenge posed by quantum computing and the increasing demand for application efficiency in Internet of Things (IoT) and Blockchain environments. Historically dominated by RSA and Elliptic Curve Cryptography (ECC), DSS now faces a significant turning point. A systematic bibliometric analysis was conducted on 2,616 documents indexed by Scopus during the 2015–2022 period, involving the analysis of Annual Scientific Production, Social Structure, and Conceptual Structure mapping using a Thematic Map. The results confirm a thematic turning point marked by a sharp acceleration in publication volume (Compound Annual Growth Rate 14.5%, peaking at 25.1% in 2020–2022), which aligns with the commencement of the Post-Quantum Cryptography (PQC) standardization process by NIST. Social structure analysis indicates a divided global role: China dominates in raw output volume, while Western countries (US, Germany, UK) act as Intellectual Hubs with the highest citation impact per document. The strongest evidence of thematic evolution is found in the Thematic Map, which empirically classifies "ECC" as a mature Motor Theme, while "Dilithium," "Lattice-based Cryptography," and "Post-Quantum Cryptography" emerge as Emerging Themes. Concurrently, "Aggregate Signature" and "Ring Signature" are identified as specialized Niche Themes. In synthesis, this study proves that the evolution of DSS is simultaneously driven by two primary factors: the external threat (quantum) and internal demands (efficiency and scalability). The findings provide a quantitative roadmap urging the global cybersecurity community to prioritize the transition to PQC standards immediately to ensure the resilience of future public key infrastructure